Mechanical Analysis of Multi-Component Tissues - Silver, Frederick H.; Shah, Ruchit G. (My University, 2017)
Collagen is the major structural fiber found in mammalian tissues. It is a protein in the form of a triple-helix which is found in several subfamilies, the most abundant of which is the fiber forming group containing Types I, II and III. Type I collagen is found in tendons, skin, cornea, bone, lung and vessel walls. This collagen is thought to give rise to the high tensile strengths of collagen fibers in tissues; in addition, it is actively involved in other physiologic processes such mechanotransduction. However, the non-linear mechanical behavior and viscoelasticity of collagen fibers make analysis of the mechanical properties of tissues complicated. Mechanistically, during mechanical loading, a tensional increase in the D period is observed with increasing strain that is associated with: 1) molecular elongation at the triple-helical level of structure; 2) increases in the gap distance between the end of one triple-helix and the start of the next one in the microfibril; and 3) molecular slippage. In this paper, we discuss the relationship between collagen hierarchical structure and its non-linear mechanical properties. Using vibrational analysis and optical coherence tomography, it is hoped that the mechanical properties of collagenous tissues can be studied in vivo in order to better understand tissue mechanics and to be better able to offer early diagnosis and differentiation of different disease states
Keywords: Collagen Fibers; Mechanical Properties.; Optical Coherence Tomography; Vibrational Analysis; Tendon; Skin; Cartilage; Elastic Arteries